DETERMINATION OF THE GROSS ALPHA AND BETA ACTIVITY CONCENTRATIONS IN SOME SELECTED CHILDREN’S DIET IN SABO, KADUNA STATE (FUDMA JOURNAL OF SCIENCES, 2023)
Twenty samples of different food brands produced locally and internationally that are commonly consumed by children were collected from the local markets in Sabo local government area of Kaduna state and analyzed using a gas proportional counter to determine the gross alpha and beta activity concentration. The results obtained showed that the average gross alpha and beta activity for the children’s diet sample was 180 Bqkg-1 and 240 Bqkg-1 respectively. These results revealed high alpha activity of eight food samples as they were above the World Health Organization (WHO) standard of 100 Bqkg-1 while for beta activity, all food samples analyzed were below the WHO standard limit of 1000 Bqkg-1. However, the results so obtained, may not pose any immediate health side effects to children consuming these product as further analysis of the specific activity is recommended.
Keywords: Food brands, Gas proportional counter, Activity, Analysis